Gender Differences in Academic Career Paths of Economists - Kahn, Shulamit (American Economic Review, 1993)
you have obtained prior permission, you may not download an entire issue of a journal or multiple copies of articles, and you may use content in the JSTOR archive only for your personal, non-commercial use. Please contact the publisher regarding any further use of this work. Publisher contact information may be obtained at